Tecnologia da informação como propulsora do aprendizado nas organizações: um estudo de caso na empresa Novelis do Brasil - Vasconcelos, Manuela Weyll (2007)
The evolution of Information Technology - IT has been demanding great changes in the corporate world. In the past ten years, IT´s development has not been limited to increasing automation, but to explore its capacity to inform, to guarantee knowledge availability, and to assure individual and organizational growth. Information was given a strategic position to ensure knowledge and apprenticeship, which are the main differentials of the organizations of the future. The goal of this essay is to analyze the perspective of managers, coordinators and users of Novelis do Brasil Ltda on the contribution of Information Technology - IT to organizational learning. A case study was completed through semi-structured interviews with managers, coordinators and users. It proved that the company is going though an important changing process that includes better utilization of resources and IT procedures with the goal of assuring knowledge availability.